Building Use Rights Over Management Rights in the Batam Free Trade Zone: A Perspective of Certainty and Legal Protection - Setiawan, Anjas; Helmi, Helmi; Rosmidah, Rosmidah (PT. Anagata Sembagi Education, 2026)
The Building Use Rights (HGB) on top of the Management Rights (HPL) is a form of state land utilization that develops in the practice of managing national strategic areas, especially in the Batam Free Trade Zone and Free Port. However, this practice raises complex juridical issues, especially related to the unclear legal status of HPL which is not explicitly regulated in the Basic Agrarian Law, thus having an impact on the weak certainty and legal protection for HGB holders. This study aims to analyze the legal status of HGB above HPL in the land management system in Batam, examine the application of Indonesian land law principles in its regulation and management by the Batam Business Agency, and formulate a reformulation of HGB regulation on HPL to ensure the protection of the rights of related parties. The research method used is normative legal research with legislative, conceptual, and systemic approaches, which are analyzed qualitatively with prescriptive reasoning. The results of the study show that the regulation of HGB above HPL is still characterized by a void and disharmony of norms, the dominance of the administrative authority of regional managers, and the application of the principles of legal certainty, justice, and protection of rights has not been optimal. This study concludes that it is necessary to reformulate the regulation of HGB above HPL through affirming the position of HPL as a state public authority, strengthening the status of HGB as a legally protected land right, and structuring the authority to manage areas to be in line with the principles of national land law and state law.